The solvothermal synthesis and characterization of quaternary arsenic chalcogenides CsTMAsQ3 (TM = Hg, Cd; Q = S, Se) using Cs+ as a structure directing agent: from 1D anionic chains to 2D anionic layers. Issue 57 (22nd September 2020) - Tian, Xin-Yu; Du, Cui-Xia; ZhaoRi, GeTu; SheLe, MuGe; Bao, Yongsheng; Baiyin, Menghe
Abstract : Presented is a method involving TM–As–Q (TM = Hg, Cd; Q = S, Se) quaternary arsenic chalcogenides and different mixed solvents which has been used to synthesize four new quaternary chalcogenide compounds. Abstract : Four new quaternary transition metal arsenic chalcogenide Cs–TM–As–Q compounds (TM = Hg, Cd; Q = S, Se) were synthesized using different mixed solvents. A 1, 4-diaminobutane(1, 4-dab)/water mixed solvent system was used to solvothermally synthesize the selenoarsenates CsTMAsSe3 (TM = Hg (1 ), Cd (2 )). In 1, the eight-membered ring anion chain consists of trigonal-planar [HgSe3 ] and trigonal-pyramid [AsSe3 ]. Compound 2 is similar to the eight-membered ring chain anion of compound 1, and [CdAsSe3 ] − further joins, through μ3 -Se and Cd, to form the layer anions [CdAsSe3 ] − . A 2-diaminopropane (1, 2-dap) and water mixed solvent system was used to synthesize two thioarsenates, Cs2 TM2 As2 S6 (TM = Cd (3 ), Hg (4 )). Compounds 3, 4 and 2 are isostructural; the Cd and Hg atoms are four coordinated. Compounds 1–4 utilize Cs + cations as a structural directing agent. Finally, the structural and optical properties of the novel series of arsenic chalcogenides were characterized.